Vascular endothelial growth factor aggravates fibrosis and vasculopathy in experimental models of systemic sclerosis - Maurer, Britta; Distler, Alfiya; Suliman, Yossra A.; Gay, Renate E.; Michel, Beat A.; Gay, Steffen; Distler, Jörg; Distler, Oliver (Annals of the Rheumatic Diseases, 2014)
High levels of vascular endothelial growth factor (VEGF), a key angiogenic factor, are present in patients with systemic sclerosis (SSc), but its role in the pathogenesis of fibrosis and its contribution to the disturbed angiogenesis of SSc remains hypothetical.Mono (+/-) and double (+/+) VEGF transgenic (tg) mice and their wildtype (wt) controls were analysed. The bleomycin model was applied to VEGF tg mice to evaluate effects of VEGF under proinflammatory conditions. Additionally, tight skin (TSK) 1/VEGF+/+ mice were generated to mimic later non-inflammatory stages of SSc.VEGF+/+, but not VEGF+/- tg mice, spontaneously developed significant skin fibrosis, indicating profibrotic effect of VEGF in a gene-dosing manner. In the proinflammatory bleomycin model, the profibrotic effect became more pronounced with induction of skin fibrosis in VEGF+/- tg mice and even more enhanced fibrosis in VEGF+/+ tg mice. Analysis in TSK1/VEGF+/+ mice showed similar profibrotic effects of VEGF also under non-inflammatory in vivo conditions. In vitro analysis revealed that VEGF is able to directly induce collagen synthesis in dermal fibroblasts. Additionally, there was an inverse gene-dosing effect on the efficacy of angiogenesis in that a higher number of microvessels was observed in VEGF+/- tg mice than in VEGF+/+ tg mice.These data provide the first evidence for VEGF as a novel molecular link between fibrosis and vasculopathy in the pathogenesis of SSc. They suggest that high levels of VEGF potently induce fibrosis in inflammatory and non-inflammatory stages, and also contribute to the relatively insufficient angiogenesis characteristic for SSc.
EVALuna2:12948